Potatoes as a Crop for Space Life Support: Effect of CO2, Irradiance, and Photoperiod on Leaf Photosynthesis and Stomatal Conductance - Wheeler, Raymond M.; Fitzpatrick, Ann H.; Tibbitts, Theodore W. (Frontiers in Plant Science, 2019)
Potatoes (Solanum tuberosum L.) have been suggested as a candidate crop for future space missions, based on their high yields of nutritious tubers and high harvest index. Three cultivars of potato, cvs. Norland, Russet Burbank, and Denali were grown in walk-in growth rooms at 400 and 800 µmol m−2 s−1 photosynthetic photon flux (PPF), 12-h L/12-h D and 24-h L/0 h D photoperiods, and 350 and 1,000 ppm [CO2]. Net photosynthetic rates (Pnet) and stomatal conductance (gs) of upper canopy leaves were measured at weekly intervals from 3 through 12 weeks after planting. Increased PPF resulted in increased Pnet rates at both [CO2] levels and both photoperiods, but the effect was most pronounced under the 12-h photoperiod. Increased [CO2] increased Pnet for both PPFs under the 12-h photoperiod, but decreased Pnet under the 24-h photoperiod. Increased PPF increased gs for both [CO2] levels and both photoperiods. Increased [CO2] decreased gs for both PPFs for the 12-h photoperiod, but caused only a slight decrease under the 24-h photoperiod. Leaf Pnet rates were highest with high PPF (800), elevated [CO2] (1,000), and a 12-h photoperiod, while growing the plants under continuous (24-h) light resulted in lower leaf photosynthetic rates for all combinations of PPF and [CO2]. The responses of leaf photosynthetic rates are generally consistent with prior published data on the plant biomass from these same studies (Wheeler et al., Crop Sci. 1991) and suggest that giving more light with a 24-h photoperiod can increase biomass in some cases, but the leaf Pnet and overall photosynthetic efficiency drops.